Україна і Центральні держави: прелюдія окупації 1918 року - Пиріг, Р. (Краєзнавство, 2018)
У статті досліджується складний процес державного самовизначення УНР, набуття статусу
суб'єкта міжнародного права, становлення взаємин з Німеччиною і Австро-Угорщиною. Висвітлено
формування договірних засад економічного і військового співробітництва з Центральними державами,
які згодом трансформувалися в економічну експлуатацію окупаційного типу. The article examines the complicated process of state self-determination of Ukraine, overcoming of federalist
beliefs by the political leadership of the Central Rada, the impact of Russian Bolshevik expansion on the
process of becoming Ukrainian People’s Republic independent, the struggle for gaining the status of a subject
of international law, the inclusion in the Brest negotiation process. The article represents the establishment of
relations with the Central States, the domination of pragmatic interests in their plans of obtaining food and
raw materials from Ukraine as a condition for the provision of military assistance, encouraging the mutual
impacts of the Brest Peace Treaty and the proclamation of State Independence of Ukraineby the Fourth Universal.
There ishighlightedthe formation of the contracts for economic and military cooperation with Germany
and Austria-Hungary, which subsequently transformed into economic exploitation of the invasion type. В статье исследуется сложный процесс государственного самоопределения УНР, приобретение
статуса субъекта международного права, становления взаимоотношений с Германией и Австро-Венгрией. Освещены формирования договорных основ экономического и военного сотрудничества с Центральными державами, которые впоследствии трансформировались в экономическую эксплуатацию
оккупационного типа.